DECOMPACTION MECHANISM OF DEEP CRYSTALLINE ROCKS UNDER STRESS RELIEF - Gorbatsevich F.F. (My University, 2003)
Within a geological massif in a stable geodynamical situation contacts on the grain boundaries in polycrystalline rocks at great depths are continuous and firm. The stress release of those rocks during drilling and excavation to the surface is accompanied by their disintegration (decompaction). The reason for the decompaction is generation of microcracks during stress release due to the difference between the elastic moduli of crystalline grains at their contacts. The mechanism of decompaction may occur not only in polymineral but in polycrystalline rocks as well. The method of decompaction evaluation of deep crystalline rocks under stress relief is presented. According to the calculations the initial manifestation of the decompaction effect in biotite gneisses will occur when they are extracted from the deep range of 0.8–1 km. The first microcracks arise on the grain borders between quartz–biotite and oligoclase–biotite. It is shown that the uplift of gneiss–granite varities of the rocks cut by the Kola superdeep borehole from depths exceeding 13–15 km will be possible in a form of separate mineral grains. Practical importance of the presented method is in an opportunity to evaluate the level of excavated decompaction. The method allow estimating the depth, from which the rock will be extracted only in a sludge form.
Keywords: Crystalline rocks; Stress release; Elastic anistropy; Decompaction; Wave velocity